1979
DOI: 10.1136/hrt.41.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postoperative left ventricular contractile function in patients with aortic valve disease.

Abstract: In 43 patients left ventricular micromanometry and cineangiography were performed preoperatively and and 20 months after aortic valve replacement. A score of left ventricular functional impairment, derived from 5 to 8 haemodynamic variables, was calculated as: number of pathological indices x 100/total number of determined indices. Preoperatively the score of left ventricular functional impairment amounted to 35 per cent in group 1 (aortic stenosis: n = 19), to 61 per cent in group 2 (combined lesion:n = 15) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

1980
1980
1988
1988

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 22 publications
2
14
0
1
Order By: Relevance
“…The present results combined with the clinical studies of Krayenbuehl et al (1979), and their unpublished studies with Mirsky, may provide a clue as to the appropriate timing of surgical/medical intervention in patients with pressure-overloaded ventricles. Krayenbuehl et al (1979) have shown in a number of pre-and postoperative studies in patients with valvular heart disease that prognosis is poor in those patients whose ventricles have overcompensated for wall mass, since their wall masses and volumes were not markedly reduced postoperatively.…”
mentioning
confidence: 60%
“…The present results combined with the clinical studies of Krayenbuehl et al (1979), and their unpublished studies with Mirsky, may provide a clue as to the appropriate timing of surgical/medical intervention in patients with pressure-overloaded ventricles. Krayenbuehl et al (1979) have shown in a number of pre-and postoperative studies in patients with valvular heart disease that prognosis is poor in those patients whose ventricles have overcompensated for wall mass, since their wall masses and volumes were not markedly reduced postoperatively.…”
mentioning
confidence: 60%
“…Patients with aortic valve disease who had residual left ventricular dysfunction after aortic valve replacement showed a significantly higher preoperative muscle mass than those with a normal or nearly normal postoperative left ventricular function. 23 In conclusion, we present evidence that in chronic pressure overload from aortic stenosis, ejection performance is not solely determined by the extent of afterload, but is also influenced by the actual inotropic state. Thus, there is no unique inverse relationship between systolic stress and ejection performance; rather, this relationship is shifted to a lower level when contractility is depressed.…”
Section: Discussionmentioning
confidence: 83%
“…15 16 The effect of aortic valve replacement on myocardial structure is, however, not yet established, and it is not known whether there is a regression of hypertrophy at the cellular level parallel to the decrease in angiographically measured muscle mass, or whether interstitial fibrosis remains unchanged after aortic valve replacement. Since myocardial structure is the major determinant of diastolic myocardial function,4 14 we determined diastolic chamber and myocardial stiffness from viscoelastic pressure-circumference and stress-strain relationships in 21 patients with aortic valve disease before and after successful valve replacement and compared these data to structural findings obtained from left ventricular endomyocardial biopsies taken during cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%